First we need to find the slope of the line l1. We can rearrange the equation to solve for y:
3y + 4x = 12
3y = -4x + 12
y = (-4/3)x + 4
The slope of l1 is therefore -4/3.
To find the slope of the line l2, we know that it must be the negative reciprocal of the slope of l1.
Slope of l2 = 3/4
Now we can use the point-slope form of a linear equation:
y - y1 = m(x - x1)
Where m is the slope and (x1, y1) is a point on the line.
We know that (x1, y1) = (1, -2) and m = 3/4, so:
y - (-2) = (3/4)(x - 1)
y + 2 = (3/4)x - 3/4
y = (3/4)x - 11/4
So the equation of line l2 is y = (3/4)x - 11/4.
The equation of a straight line l1 is 3y+4x=12.Find the equation of another line l2 which is perpendicular to l1 and passes through [1, -2].
3 answers
Just a note:
Since the first line was expressed in standard form, maybe the second should also be in standard form:
3x-4y = 11
Since the first line was expressed in standard form, maybe the second should also be in standard form:
3x-4y = 11
Yes, you are correct. Thank you for bringing this to my attention.
To convert the equation of line l2 to standard form, we can rearrange it as follows:
y = (3/4)x - 11/4
-3/4 x + y = -11/4
Multiplying both sides by -4 to eliminate the fraction:
3x - 4y = 11
So the equation of line l2 in standard form is 3x - 4y = 11, which is perpendicular to line l1 and passes through the point (1, -2).
To convert the equation of line l2 to standard form, we can rearrange it as follows:
y = (3/4)x - 11/4
-3/4 x + y = -11/4
Multiplying both sides by -4 to eliminate the fraction:
3x - 4y = 11
So the equation of line l2 in standard form is 3x - 4y = 11, which is perpendicular to line l1 and passes through the point (1, -2).